Hockey's record breakers - Frederick, Shane (North Mankato, Minnesota : Capstone Press, 2017)
"Wayne Gretzky skated down and shattered many of pro hockey's best-known records, and ever since superstars such as Mario Lemieux, Sidney Crosby, and Alex Ovechkin have pursued his amazing marks. Here are hockey's greatest records and stories of the players who have held, chased, and broken them." --
Includes bibliographical references and index.
1040L
Accelerated Reader AR
Keywords: Hockey -- Records -- Juvenile literature; Hockey players -- Biography -- Juvenile literature